Experimental study of flow forces on hydraulic poppet valve [electronic resource] - Neo, Hong Jian, 1988-, author; Yahaya Ramli, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012